Enhanced Efficiency and Power Density in Next-Gen Power Electronics Through Zero Overvoltage Switching - Schmied, Nico; Kerscher, Moritz; Matlok, Stefan; Eckardt, Bernd; März, Martin (2025 Energy Conversion Congress & Expo Europe (ECCE Europe), 2025)
High-voltage power electronics, utilizing wide-bandgap devices, can realize superior efficiency and power density designs compared to silicon-based power electronics. The fast switching transitions of those devices lead to higher overvoltage peaks and voltage oscillations. Zero Overvoltage Switching (ZOS) combines the fast switching speed of wide-bandgap devices with the prevention of voltage oscillations. This paper examines the advantages of ZOS through the example of a dc-dc converter. It presents a simulation method that simulates the channel current inside the transistor, allowing further analysis of the resulting switching losses. For the first time, a comparison of switching losses is possible between a converter that applies ZOS and a conventional switching converter. The difference in switching losses is reflected in the efficiency difference measured on a 30 kW dc-dc converter prototype. Under identical operating conditions, ZOS achieves 47.4% lower losses at full load compared to the conventional switching varian